"Questionnaire of parents' opinions on digital games in the education of children with autism spectrum disorder" in a Greek context - Chaidi, Irene; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
In recent years worldwide, the use of Information and Communication Technologies (ICT) contributes significantly to the learning process, especially for students with special needs, arguing that a special aspect of ICT in the digital game, as it can be a part from a means of entertainment and personal satisfaction of each student, an excellent tool for their education. Also, Research from the National Coalition for Parent Involvement in Education shares that "no matter their income or background, students with involved parents are more likely to have higher grades and test scores, attend school regularly, have better social skills, show improved behavior and adapt well to school.”, especially in the specialty of people with autism. In the work that follows, parents' views on educating their children with ASD using a digital game are recorded.